ETIO-PREVALENCE OF SUB CLINICAL MASTITIS IN HOLSTEIN X HARYANA CROSSBRED CATTLE - Anirban Guha; Sandeep Gera (Exploratory Animal and Medical Research, 2011)
The purpose of the investigation was to evaluate the efficacy of Somatic cell count (SCC), California mastitis test (CMT) and Chloride test in detecting SCM and study its etioprevalence in Holstein X Haryana cattle. SCC prevalence for SCM, latent infected quarters and non-specific infected quarters were found to be 28.63%, 8.63% and 6.67%, respectively, when divided on the basis of International Dairy Federation criteria. Staphylococcus sp. (47.37%) and Streptococcus sp. (33.68%) was most prevalent bacterial agent. The present study revealed that CMT in conjunction with SCC is better to diagnose SCM than alone.